Omalizumab Treatment in Chronic Spontaneous Urticaria During Pregnancy: Report of A Case and Review of the Literature - SALMAN, ANDAÇ; AKTAŞ, MERYEM (BILIMSEL TIP YAYINEVI, 2021)
Omalizumab is a safe and effective treatment option for chronic spontaneous urticaria (CSU). Although cohort studies in patients with asthma show no increased risk of congenital abnormalities, very little data exist in the literature regarding the use of omalizumab for CSU during pregnancy. Herein, the safe and successful use of omalizumab updosing in a pregnant woman with CSU along with a review of the published literature is presented.
Keywords: Chronic spontaneous urticaria; omalizumab; pregnancy; updosing